Inovasi Organisasi Publik: Implementasi Knowledge Management Mendorong Inovasi - Achmad Nurmandi (Magister Administrasi Publik, 2006)
This paper drives from the environment risk and knowledge literature a model that integrates organizational form and epistemological of public agencies responsible for addressing innovation. Practically, the model in making connections between knowledge management and innovation and provides public agencies manager with a systematic framework for relating democratic context knowledge production processes to particular local government organization.